Bypass in urban space: creative scenarios - Sarı, Tüba; Aras, Aylin; Yılmaz S.Z. (Kauno Technologijos Universitetas, 2021)
Considering functional and experiential congestion in Kadıköy, the paper deals with the concept of “Bypass in Urban Space” in the context of the user-centred design. The case study is limited with the axis extending from Söğütlüçeşme and General Asım Gündüz Street which is connected to the main artery. Kadıköy, as one of the rapidly growing and transforming urban centres in Istanbul, reflects variable traumas in terms of human-environment behaviour relationships. A research model is developed to identify these traumas and produce a solution through bypassing the congestion in the area. Within the scope of the study, it is aimed to contribute to the dynamic structure of the city by creating new functional experience spaces in the capillary streets. On the other hand, it is aimed to design the spaces that lead the user to stop and perceive the environment beyond its transition function of the main artery within the dense pedestrian and vehicle traffic. By the research model, it is suggested multi-functional creative scenarios through the problems and hypotheses identified within the framework of the user-environment connection. Environmental and behavioural research, conceptual readings, sketch of ideas and visualization of conceptual studies, the designer scenarios are the main phases of the research as well as developing a proposal within the scope of contribution to the field. Most of design solutions analyses several dynamics such as bypass, main artery, in-between space, spatial conjunction, integration in urban space. So, it is aimed to design integrative mobile spaces for continuity of user-environment relationship beyond establishing a physical and visual connection.
Keywords: In-between space; Integration; Main artery; Spatial conjunction; Urban bypass SciVal TopicsLearn about these Topics